Final answer:
To find the inverse function of y=3^x, you take the logarithm with base 3 of both sides, yielding x=log3(y), and then interchange x and y to get the inverse function y=log3(x). This process demonstrates how operations are reversed to solve for the original variable, akin to the ideas presented in the Ancient Puzzle.
Step-by-step explanation:
The Ancient Puzzle, when related to the inverse function for the exponential equation y=3x, emphasizes the process of reversing operations to solve for the original value. Given an exponential function like y=3x, the inverse would be an operation that allows us to find x given a value of y. In the context of exponential functions and their inverses, taking the logarithm of both sides is the method used to achieve this.
In this case, to find the inverse of y=3x, we would take the logarithm with base 3 (logarithm base 3 is denoted as log3), which would give us:
x = log3(y)
Since we need an equation in y= form for the inverse, we simply interchange x and y to get:
y = log3(x)
This equation represents the inverse function of y = 3x, which is crucial since exponential functions and their inverses, such as the natural logarithm (ln) or logarithm base 10, "undo" each other.